THE STUDY OF LANGUAGE USE IN BILINGUAL CLASSROOM LEARNING (STUDY IN THE MIN 1 CIPUTAT) - Nuryani .; Nafia Wafiqni (Al-Bidayah : jurnal pendidikan dasar Islam, 2020)
The purpose of this research is to describe the use of language by teachers and students in bilingual classroom learning at Madrasah Ibtidaiyah Negeri (MIN) I Ciputat, South Tangerang. This research emerged based on the recent rise in the number of bilingual classes, such as Indonesian, English, and Arabic, which led to the use of learning activities such as code-switching. Based on the analysis, the authors concluded that generally, teachers use two or more languages consisting of Indonesian, foreign (English and Arabic), and regional languages. The use of Indonesian dominates in learning in accordance with the national curriculum, while the use of English dominates in subjects in line with the Cambridge Curriculum. Therefore, the use of foreign languages in these two learning activities aims to familiarize students with the ability to hear and speak foreign languages. These activities tend to improve student’s linguistics competence.